2010
DOI: 10.1161/circulationaha.109.866343
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long-Term Right Ventricular Pacing in Young Adults With Structurally Normal Heart

Abstract: Background-Right ventricular pacing increases the risk of heart failure in adults with structural heart disease. The impact of prolonged right ventricular pacing in adults without structural heart disease is not fully characterized and may depend on interactions of pacing with abnormal substrate predisposing to ventricular dysfunction. Methods and Results-We assessed the effect of right ventricular pacing in patients who underwent pacemaker implantation for isolated congenital atrioventricular block between 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 32 publications
2
23
1
1
Order By: Relevance
“…In addition, the presence of left ventricular dysfunction has been reported as an independent predictor of a deleterious clinical impact of PPI, 32,33 whereas LVEF remained stable over time in most patients without structural heart disease receiving a PPI. 34 However, we did not find differences between patients with and without PPI when analyzing the data by subgroups according to left ventricular function. The severity of comorbidities and concomitant structural heart disease in patients undergoing TAVI led to a high rate of death and heart failure, and this might mitigate the potential negative effect of PPI in these patients.…”
Section: Ppi After Tavi and Clinical Outcomescontrasting
confidence: 55%
“…In addition, the presence of left ventricular dysfunction has been reported as an independent predictor of a deleterious clinical impact of PPI, 32,33 whereas LVEF remained stable over time in most patients without structural heart disease receiving a PPI. 34 However, we did not find differences between patients with and without PPI when analyzing the data by subgroups according to left ventricular function. The severity of comorbidities and concomitant structural heart disease in patients undergoing TAVI led to a high rate of death and heart failure, and this might mitigate the potential negative effect of PPI in these patients.…”
Section: Ppi After Tavi and Clinical Outcomescontrasting
confidence: 55%
“…It should be highlighted that not all patients develop LV dyssynchrony and newonset heart failure after RV pacing. Therefore, early predictive factors (Zhanget al, 2008;Siu et al,2008 ;Sagar et al, 2010), such as dyssynchrony at the time of implantation, paced QRS width, age, presence of atrial fibrillation, concomitant coronary artery disease, or compromised LVEF, or antibody status should be further evaluated, they may reveal the patients who are more prone to LV function deterioration and who are consequently better candidates for biventricular pacing. CRT use with milder degrees of LV dysfunction or even normal cardiac function as a means of maintaining cardiac mechanical synchrony is at this date, controversial.…”
Section: Resultsmentioning
confidence: 99%
“…25-29 Indeed, a study reported on the relationship between the presence of antibodies and development of DCM. 30 In another report, pacing at high heart rates was hypothesized to cause DCM. 31 Others have mentioned that the pacing site was related to developing detrimental ventricular remodeling.…”
Section: Discussionmentioning
confidence: 99%